The variation in the level of the socio-economic development of the NUTS-3 subregions in the European Union - Spychała, Marcin (Publishing House of Wroclaw University of Economics and Business, 2023)
A very important research problem is the specification of the level of the socio-economic development of the EU regions. Within the cohesion policy, one may differentiate between regions more and less advanced in terms of general development, including the worth of GDP per capita. Following that measure, one can establish the areas eligible for getting help from EU budget support programmes. The purpose of the article was to present the variation in the level of the socio-economic development of 28 EU countries within the 1,347 NUTS-3 units. The level of the development was established on a multilevel basis, subcategorising three factors of regional development: human capital, the natural environment and the economy. The article specifies the extent of the NUTS-3 unit general progression following the analysis of 31 indicative measures structured around publicly available Eurostat statistical data (as of 2019). The extent of the progression was demonstrated based on a synthetic measure revealing the taxonomic distance of a particular region from the assumed arrangement measuring the development. The research procedure consisted of five development levels, namely: the establishment of factors of the progression of regions, a choice of variable factors, a decrease in the multi-factor space, an identification in the extent of the social and economic progression of the researched units and a subcategorisation of the units on the scale of the social and economic progression structured around a ranking prepared using the analysis of a lowering synthetic measure. The research resulted in spatial variation of 1,347 NUTS-3 unit subregions in 28 EU states presented in terms of the level of the social and economic progression and the three subparts of the progression. The highest synthetic measure was noted in the areas including the capitals of the states included in the research and in a belt comprising the Irish subregions, Central England, the Benelux states, Western and Southern Germany, up until the Alpine subregion. Moreover, significant differences between the levels of the development within the respective states were presented. The results of the research may be a source of inspiration for EU institutions within the scope of the manner of specifying the richest and the poorest EU regions, whose purpose is to ensure the efficient introduction and conclusion of the cohesion policy in the programming periods specified.
Argumenta Oeconomica, 2023, Nr 1 (50), s. 179-203
Keywords: regional development; NUTS-3 units; developmental discrepancies; distance from the pattern; Hellwig’s data reduction